Antitrust law symposium. - New York State Bar Association. Antitrust Law Section (Chicago, Commerce Clearing House., 1952)
Includes proceedings of the annual meeting.
Some issues have also a distinctive title.
Index to legal periodicals
Keywords: Antitrust law -- United States